INFLUENCE OF PIRENZEPINE ON GALLBLADDER CONTRACTION IN MAN INDUCED BY SHAM FEEDING OR AN INTRADUODENAL MEAL - YEGEN, BERRAK (KARGER, 1992)
Pirenzepine, an M1 muscarinic receptor antagonist, was tested for its ability to antagonize sham feeding- and intraduodenal fatty meal-stimulated gallbladder contraction in man. Intravenously administered pirenzepine abolished sham feeding-induced gallbladder contraction. Pirenzepine also inhibited contraction induced by intraduodenal meal, but this inhibition was of a lesser magnitude than the inhibition of sham feeding-induced contraction. The results demonstrate that the cephalic phase of gallbladder contraction is probably mediated by M1 muscarinic receptors while the duodenal phase of gallbladder contraction is partially mediated by M1 receptors.
Keywords: PIRENZEPINE; GALLBLADDER CONTRACTION; SHAM FEEDING; MEAL-STIMULATED CONTRACTION; MUSCARINIC RECEPTORS; CHOLECYSTOKININ; MUSCARINIC RECEPTOR SUBTYPES; GUINEA-PIG GALLBLADDER; CHOLECYSTOKININ RECEPTORS; PANCREATIC-SECRETION; OPOSSUM GALLBLADDER; CHOLINERGIC SYSTEM; ATROPINE; HUMANS; STIMULATION; DOGS